(untitled) (Teología, 2017)
In this article I will present some results of an investigation about practices of popular spirituality in the Hospice San Camilo. From the perspective of spiritual theology and after defining what I mean by spiritual guidance, especially in the end of life, I will make a brief introduction about the nature of palliative care. Then, I will describe the nature of Hospice care, particularly in the “House of Hope” (Hospice San Camilo). Finally I will discuss some features of this spiritual accompaniment, paying particular attention to the comprehensive, competent and compassionate nature of this kind of guidance, expressed in a special care. Finally I propose the metaphor of the wounded healer as a model of this support.